Gardening at Deir el-Bersha in the middle kingdom a unique representation of cucurbitaceae cultivation - Hudáková, Lubica 1985- (2016)
Decoration in the tombs of Middle Kingdom officials often resembles a jigsaw puzzle because many of them have suffered damage, both from natural disasters and human intervention, and their scenes are often preserved only in fragments. This applies to the tomb of Djehutyhotep II at Deir el-Bersha, dating to the second half of the 12th Dynasty, and especially to the right-hand wall of the inner chamber, which was once decorated with scenes related to agriculture, food production, wine-making, gardening and crafts. The present paper examines a set of tiny fragments from this wall that are now kept in the British Museum, which show the cultivation of a plant from the Cucurbitaceae family with the aid of a trellis. The plant depicted there can probably be identified with the vegetable melon (Cucumis melo), a popular vegetable crop. The illustration is unparalleled in Egyptian art, and may be considered an innovation of the Middle Kingdom.
Keywords: Djehutyhotep II; Cucumis melo; BM EA 71520; BM EA 71525; BM EA 71528; Fruits; Cucumbers; Kingdom of Egypt; Desserts; Ancient Egypt; Illustration; Leaves; Iconography; Seeds; Deir el-Bersha